The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/iid3.986
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic values of serum BNP, PTX3, and VEGF in acute pulmonary embolism complicated by pulmonary artery hypertension and their correlations with severity of pulmonary artery hypertension

Qinghou Zheng,
Bin Zhang,
Na Lu
et al.

Abstract: ObjectiveThis paper aimed to unveil the diagnostic values of serum brain natriuretic peptide (BNP), pentraxin 3 (PTX3), and vascular endothelial growth factor (VEGF) in acute pulmonary embolism complicated by pulmonary artery hypertension (APE‐PAH) and their correlations with severity of PAH.MethodsA total of 153 patients with APE were selected for our study and divided into the PAH and Non‐PAH groups according to the measurement of pulmonary artery pressure by echocardiography. Serum BNP levels were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…Singh et al 21 discovered that in patients undergoing non-cardiac surgery with hypertension and diabetes, preoperative and postoperative serum BNP levels are significantly elevated, making BNP an important predictor for perioperative and postoperative complications, hospital stay, and mortality rates in these patients. Zheng et al 22 found that BNP is significantly overexpressed in the serum of patients with acute pulmonary embolism combined with pulmonary hypertension, and its expression increases with the severity of pulmonary hypertension, having high diagnostic value for the disease, and correlates positively with disease severity, serving as a predictive marker for the severity of the condition. Our study found that the serum levels of BNP in the severe group before and after treatment were significantly higher than those in the mild group; the expression levels in the serum after treatment were significantly lower than before treatment; and the expression levels in the serum of the death group after treatment were significantly higher than those in the survival group, suggesting that BNP reflects cardiac functional changes due to stress in patients and is one of the reasons for worsening conditions, poor therapeutic effect, and poor prognosis in pneumonia patients.…”
mentioning
confidence: 99%
“…Singh et al 21 discovered that in patients undergoing non-cardiac surgery with hypertension and diabetes, preoperative and postoperative serum BNP levels are significantly elevated, making BNP an important predictor for perioperative and postoperative complications, hospital stay, and mortality rates in these patients. Zheng et al 22 found that BNP is significantly overexpressed in the serum of patients with acute pulmonary embolism combined with pulmonary hypertension, and its expression increases with the severity of pulmonary hypertension, having high diagnostic value for the disease, and correlates positively with disease severity, serving as a predictive marker for the severity of the condition. Our study found that the serum levels of BNP in the severe group before and after treatment were significantly higher than those in the mild group; the expression levels in the serum after treatment were significantly lower than before treatment; and the expression levels in the serum of the death group after treatment were significantly higher than those in the survival group, suggesting that BNP reflects cardiac functional changes due to stress in patients and is one of the reasons for worsening conditions, poor therapeutic effect, and poor prognosis in pneumonia patients.…”
mentioning
confidence: 99%